Dust Concentration Changing Regularities and Dust Reduction Technology by Spray Negative Pressure in Fully Mechanized Mining Face - Lirong Wu; Hongxuan Chen; Jiamin Li; Shican Fu; Yuyan Zhuang (Geofluids)
The dust concentration changing regularities are the basis to take dust depression measures, which is greatly influenced by the airflow. In the software of FLUENT, the value of ventilation velocity is set as a constant, which cannot express the real ventilation. According to the flow characteristics of the sublayer and data from Nicholas’ experiment, the ventilation velocity distribution formula of sublayer in the inlet section of fully mechanized caving coal face is deduced. The boundary condition of velocity is given by UDF. Taking the 3top1110 fully mechanized caving coal face as an example, the dust distribution in the process of coal mining and hydraulic support shifting was studied. According to the dust-spray coupling experiment, three types of nozzle are chosen based on the efficiency of dust suppression. Combining the dust migration rule and the characteristics of nozzles, the negative pressure-secondary dust suppression devices of spray were developed and applied. And the above measures have lowered the dust concentration effectively.